Factual Analysis of Educational Laboratory Management at SMAS Brigjend Katamso II Medan - Sihotang, Winda; Zainuddin, Zainuddin; Rahman, Arif (Borong Newinera Publisher, 2024)
This study examines the comprehensive management practices of educational laboratories at SMAS Brigjend Katamso II Medan, focusing on maintenance, safety protocols, human resources, and stakeholder insights. Utilizing theoretical frameworks such as risk management, constructivist learning, and human capital theories, the analysis reveals a proactive approach to equipment maintenance, rigorous safety standards, and skilled human resources. Findings indicate robust preventive maintenance schedules, frequent safety training sessions, and qualified staff contributing to effective laboratory operations. Stakeholder feedback emphasizes the importance of well-equipped facilities, integrated curriculum approaches, and continuous professional development for educators. Recommendations include diversifying laboratory activities, expanding professional development opportunities, enhancing collaboration between staff and teachers, and strengthening safety protocols. By implementing these strategies, SMAS Brigjend Katamso II aims to foster a safe and engaging environment that supports student learning and success in STEM disciplines.